2016
DOI: 10.1007/s00216-016-9727-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted extraction combined with dispersive liquid–liquid microextraction (US-DLLME)—a fast new approach to measure phthalate metabolites in nails

Abstract: A new, fast, and environmentally friendly method based on ultrasound assisted extraction combined with dispersive liquid-liquid microextraction (US-DLLME) was developed and optimized for assessing the levels of seven phthalate metabolites (including the mono(ethyl hexyl) phthalate (MEHP), mono(2-ethyl-5-hydroxyhexyl) phthalate (5-OH-MEHP), mono(2-ethyl-5-oxohexyl) phthalate (5-oxo-MEHP), mono-n-butyl phthalate (MnBP), mono-isobutyl phthalate (MiBP), monoethyl phthalate (MEP), and mono-benzyl phthalate (MBzP)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It should be noted, however, that some phthalates, especially DBP, are used in nail polishes and that care should be exercised in interpreting such measurements. MEHP, MBP, and MEP were the major metabolites detected in every nail sample, with a median concentration of 138, 74, and 64 ng/g, respectively [135]. Another study of nail samples from Oslo, Norway, showed the presence of monoesters, such as MMP (geometric mean 89.7 ng/g), MEP (104.8 ng/g), and MBP (89.3 ng/g) [112].…”
Section: Biomonitoring Of Phthalatesmentioning
confidence: 99%
“…It should be noted, however, that some phthalates, especially DBP, are used in nail polishes and that care should be exercised in interpreting such measurements. MEHP, MBP, and MEP were the major metabolites detected in every nail sample, with a median concentration of 138, 74, and 64 ng/g, respectively [135]. Another study of nail samples from Oslo, Norway, showed the presence of monoesters, such as MMP (geometric mean 89.7 ng/g), MEP (104.8 ng/g), and MBP (89.3 ng/g) [112].…”
Section: Biomonitoring Of Phthalatesmentioning
confidence: 99%
“…Similarly to Giovanoulis et al 33 in which the same urine and finger nail sample extracts were used for the quantification of phthalate and DINCH metabolites, field (n 1 = 10) and procedural blanks (n 2 = 5) were analyzed for each extraction method without any phthalate contamination problems. 25,26,31 2.5. LC/ESI-Orbitrap-MS Analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Until analysis all samples were stored at −20 °C. Before the extraction, residues of nail polish and dirt were cleaned from the nails using acetone, as previously described. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations